Zero Trust Architecture Research Trends: A Bibliometric Study - Loso Judijanto; Rizki Dewantara (Westscience Press, 2026)
Rapid evolution of cyber threats, cloud computing and digital transformation have led to increased need for adaptive and resilient cybersecurity framework. Zero Trust Architecture (ZTA) has been developed as an advanced security model that is designed to overcome limitations of the existing approaches based on perimeter-based security through its features of continuous verification, least-privilege access, and identity-centric protection. This paper is devoted to analyzing the global research development, intellectual structure and trends of Zero Trust Architecture through the use of bibliometric analysis methodology. The data for analysis were collected from Scopus database by means of keywords relating to “Zero Trust Architecture” and “Zero Trust Security” and then were analyzed using VOSviewer tool. The aspects that are covered by the analysis include the dynamics of publications, citation impact, influential authors, international and country collaboration, co-occurrence of keywords, themes and research patterns. It can be concluded from the findings that ZTA research has expanded greatly and is mostly concentrated on topics of network security, authentication, trusted computing, network architecture, and access control. Also, the recent trends in ZTA research indicate increased use of ZTA in combination with new technologies, including artificial intelligence, machine learning, blockchain, IoT, federated learning and cloud computing. Collaboration analysis reveals the international and interdisciplinary character of ZTA research, which involves contributions from different countries, scientific institutions and cybersecurity communities. The results of the research allow understanding the evolution of ZTA and identifying future opportunities in the area of intelligent, adaptive and decentralized cybersecurity architectures.